A review of the clinical characteristics and management of immunosuppressed patients living with HIV or solid organ transplants infected with SARS-CoV-2 omicron variants - Song, Yan; Lou, Lixin; Zhang, Kaiyu (Frontiers in Public Health, 2024)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) omicron strain was first detected in South Africa in November 2021. Although clinical responses to SARS-CoV-2 depend on host immunity, it remains uncertain how immunosuppression affects subsequent coronavirus disease 2019-related (COVID-19-related) incidence, severity, and mortality, especially with respect to the omicron strain. Conversely, immunosuppressants are often thought to predispose to infection. To explore the associations between host immunity and infection with SARS-CoV-2 omicron variants, here we discuss two groups of immunosuppressed patients: organ transplant recipients, who generally receive exogenous immunosuppressants, and Human Immunodeficiency Virus (HIV)-infected patients, who often have disease-related immunosuppression. In summarizing the clinical features and prognoses of HIV-infected patients and human organ transplant recipients infected with SARS-CoV-2 omicron variants, we provide new insights into the pathogenesis of omicron SARS-CoV-2 and provide a framework for the management of these patients now and in the future.